2011
DOI: 10.1016/j.jval.2011.05.021
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Organic and Functional Dyspepsia on Work Productivity: The HEROES-DIP Study

Abstract: Our study showed an important influence of dyspepsia on work productivity. We did not find any statistically significant difference on the influence on work between patients with organic dyspepsia and functional dyspepsia. The social impact of these findings is underscored by taking into account the prevalence (up to 40%) of this condition in Brazil.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(58 citation statements)
references
References 20 publications
1
53
0
4
Order By: Relevance
“…Similarly, a case control study [50] conducted at Noble Higher Clinic; Addis Ababa, Ethiopia using non-invasive tests (H. pylori stool antigen) showed that there was a significant difference between dyspeptic and non-Dyspeptic participants. Even though, many studies [32,[51][52][53] conducted to investigate the association between Dyspepsia and H. pylori on rapid antibody, almost all found that H. pylori infection was significantly associated with Dyspepsia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, a case control study [50] conducted at Noble Higher Clinic; Addis Ababa, Ethiopia using non-invasive tests (H. pylori stool antigen) showed that there was a significant difference between dyspeptic and non-Dyspeptic participants. Even though, many studies [32,[51][52][53] conducted to investigate the association between Dyspepsia and H. pylori on rapid antibody, almost all found that H. pylori infection was significantly associated with Dyspepsia.…”
Section: Discussionmentioning
confidence: 99%
“…There are studies that showed the seroprevalence of H. pylori in different countries. These studies found that the prevalence vary with geographic location, ethnicity, and demographic factors of the studied population [32]. Studies revealed that the prevalence increases in dyspeptic patients than non dyspeptic individuals and dyspeptic symptoms account 10% of hospital admission in Ethiopia [33].…”
Section: Introductionmentioning
confidence: 94%
“…Health economic data indicate that functional dyspepsia has high direct and indirect costs, specifically driven by the high prevalence of comorbidity 18,43 , but both organic dyspepsia and functional dyspepsia have similar economic effects 44 .…”
Section: Epidemiologymentioning
confidence: 99%
“…The most widely used generic measure, the Short Form 36-Item Health Survey (SF-36) 222 , assesses eight dimensions of health: physical functioning, social functioning, Nature Reviews | Disease Primers Fatty foods , milk and dairy Alcohol , coffee Red meat Carbonated drinks Vegetables Spicy foods Carbohydrates and wheat (37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53) Citrus (30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46) Figure 5 | Foods and food groups frequently associated with symptom induction or exacerbation in functional dyspepsia. Offending foods reported by patients with functional dyspepsia include fatty food (for example, fried food [179][180][181]187,191 ), alcohol 179,180 , dairy products 179,181 , coffee [179]…”
Section: Quality Of Lifementioning
confidence: 99%
“…2 Up to 40% of persons who have functional dyspepsia consult a physician, 3 and the condition negatively affects attendance and productivity in the workplace. 4 Functional dyspepsia has substantial financial implications for patients, health care organizations, and society as a whole; costs associated with the condition in the United States in 2009 were in excess of $18 billion. 5 It is therefore important that physicians be able to recognize functional dyspepsia, use investigations and diagnostic tests judiciously, and recommend effective treatments, in order to minimize the potential adverse social and economic effects of the condition.…”
mentioning
confidence: 99%